Electron-induced vibrational transitions in N2+. (27th March 2015) - Fifirig, Magda
Abstract: We have investigated the vibrational excitation and de-excitation of with electrons of energy below 1 eV. Computations have been performed using the multichannel quantum defect theory with a second-order perturbative evaluation of the K reaction matrix. Assuming a Maxwellian electron-energy distribution, the corresponding rate coefficients were also determined.